Improving the Creativity and Competitiveness of Craft MSMEs Through HR Training and Digital Marketing - Rahayu, Yayu Sri; Suparwo, Adi (Economics, Business, Accounting & Society Review, 2025)
Human resource quality and digital readiness are increasingly recognized as crucial foundations for strengthening creativity and competitiveness among Micro, Small, and Medium Enterprises (MSMEs). However, many craft-based MSMEs still struggle to optimize human resource potential and adapt to technological changes in marketing, resulting in limited innovation and slow competitive growth. This study aims to analyze the influence of HR training and digital marketing on the creativity and competitiveness of craft MSMEs in Pengkolan Village, Cikidang Village, Lembang District, West Bandung Regency. A quantitative method was employed using a descriptive and verification approach, with survey-based data collected through purposive sampling of MSME actors. Data were analyzed through validity and reliability testing, multiple linear regression, and the coefficient of determination using SPSS version 29. The results reveal that HR training has a significant positive effect on MSME creativity and competitiveness, indicating that improved knowledge, skills, and attitudes directly contribute to stronger innovative capacity. Digital marketing also shows a significant positive influence, demonstrating that effective online promotion enhances consumer reach, purchasing tendencies, and overall market responsiveness. Together, HR training and digital marketing explain 67.4% of the variation in MSME creativity and competitiveness, indicating their substantial combined contribution. These findings imply that strengthening human resource development and digital marketing adoption is essential for advancing the innovation capabilities and long-term competitiveness of craft MSMEs.